Production of intracellular recombinant bromelain by Escherichia coli BL21-AI using shake flask and stirred tank bioreactor - Jamaluddin, Mohd Jamil Aizat; Amid, Azura (IIUM Press, International Islamic University Malaysia, 2017)
The optimization of recombinant protein production by Escherichia coli (E. coli) is an important first step to ensure economic feasibility and realization towards a sustainable future commercialization prospects. Bromelain, a protease native to pineapple plant species, is one of the commercially important therapeutic enzymes. In the field of bromelain research, production of recombinant Bromelain (recBromelain) using E. coli BL21-AI is one of the most recent novel developments to provide a more robust alternative as compared to conventional extraction approaches. Based on previous studies, the recBromelain indeed had proteolytic potency as effective as commercial bromelain. However, judging from the level of protein expression, the recBromelain productivity using E. coli BL21-AI expression system was too low to be considered for commercialization. It has been well established that suboptimal fermentation medium and process parameters which directly affect the growth of E. coli are among primary causes behind low recombinant protein expression. Optimization studies on these two aspects were therefore warranted and sought to fill the gap left unexplored from previous studies. Statistical design of experiments based on Plackett-Burman, Factorial design, One-Factor-at-a-Time and Response Surface Methodology were employed to identify significant few of E. coli growth parameters that affected recombinant bromelain productivity. Studier autoinduction medium was used as the basis for fermentation medium optimization as the medium produced highest crude recBromelain specific activity during preliminary media screening in shake flask. Analysis of variance (ANOVA) shows that concentration of tryptone, NH4Cl, and CoCl2 affected specific activity the most where at 14% (w/v), 153.4 mM and 0.4 μM, respectively, they significantly improved specific activity by 350% as compared to original autoinduction medium performance. Tryptone and NH4Cl ensured abundant nitrogenous elements used as the building blocks to sustain cell growth. CoCl2 was a vital metal cofactor in E. coli cellular enzymatic machinery but inevitably became toxic at higher concentration. A more economical alternative which used a low level of tryptone (4% w/v) was significantly reduced the medium cost by 68% at the expense of a reduced degree of improvement (130%) in crude specific activity. The effects of fermentation process parameters were investigated using 2-L stirred tank bioreactor using the improved media composition. ANOVA shows that dissolved oxygen tension (DOT), aeration, and reduction temperature had the most significant effect on specific activity. The highest level of specific activity was found at 35% DOT, 1 vvm, pH 7.4 and 30°C where the value was comparable as in optimized shake flask culture. At these conditions, a lower specific growth rate was achieved where it promoted better protein folding as compared to higher growth rate. Finally, attempt to increase recBromelain production volume further using 30-L bioreactor was made using constant impeller tip speed and constant oxygen transfer coefficient (kLa) to determine the best range for impeller tip speed. A range of impeller tip speed range between 0.47 – 0.86 m/s under constant kLa produced a more comparable specific activity as obtained from 2-L stirred tank bioreactor production. This confirmed that oxygen transfer was a limiting factor in aerobic culture owing to the low solubility of oxygen in the fermentation broth and insufficient mixing when dealing with high cell density cultures of fast-growing E. coli.